Jewish Poets, Greek Poetry: Language and Identity in the Hellenistic Jewish Poetic Tradition - Dhont, Marieke (Biblische Notizen, 2021)
Ezekiel’s Exagoge is a literary work on the crossroads of the Jewish and Greek traditions. As a result, this work is an excellent gateway into the discussion of how scholarship understands the Jewish-Greek encounter, which has not always been received positively in the past. In this article I engage in a close-reading of the language and form of the text itself, contextualize it among other Jewish-Greek poetic works, and reflect on what we may infer from it about Greek-speaking Judaism.